Effects of 3D-printed Customized Gloves on the Performance of Wheelchair Racers - Hyoung-Kuy Roh; Gun-Hwan Bae (Korea Institute of Sport Science, 2024)
PURPOSE This study seeks to contribute to the enhancement of the performance of domestic wheelchair racers by producing 3D-printed customized gloves and verifying their application effect. METHODS A total of three male wheelchair racers who belong to the T54 and have won gold medals in the National Para Games within the last three years were selected as subjects. Each subject performed three session s of muscle activity and maximum speed measurements before and after applying a 3D-printed glove during the stroke and recovery phases of wheelchair racing, focusing on the pectoralis major (PM), triceps brachii (TB), and erector spinae (ES) muscles. To standardize the muscle activity measurement data, the relative muscle activity level (%) for each section was calculated by maximum voluntary isometric contraction (MVIC) for each subject. All maximum speeds of each round of driving were calculated by the average record for comparative analysis. In addition, to verify the effectiveness of applying the 3D-printed glove, the Wilcoxon signed rank test, which is a non-parametric test method, was performed on all measured values using SPSS 24.0. RESULTS This study derived the following results. First, a statistically significant difference was observed in the muscle activity of each major muscle before and after using the 3D-printed glove. In common, an increase in muscle activity of the PM, TB, and ES was confirmed in the stroke section, and an increase in muscle activity of the TB was confirmed in the recovery section. Second, a statistically significant difference was documented in the maximum speed before and after using the 3D-printed glove. When using 3D-printed gloves, the maximum speed increased by 4.57, 3.63, and 1.06km/h for Payer A, and by 5.9, 6.04, and 7.86km/ h for Player B. In the case of Player C, the speed increased by 6.73, 2.27, and 0.83km/h, and all three players improved their maximum speed through the 3D-printed gloves. CONCLUSIONS Our study suggests that the application of 3D-printed customized gloves can have a positive impact on the performance of wheelchair racers. If the application of 3D-printed customized equipment is extended to athletes in a wider range of sports in the future, this could significantly contribute to the improvement of performance in domestic disability sport.